2022
DOI: 10.1200/jco.2022.40.17_suppl.lba1
|View full text |Cite
|
Sign up to set email alerts
|

Panitumumab (PAN) plus mFOLFOX6 versus bevacizumab (BEV) plus mFOLFOX6 as first-line treatment in patients with RAS wild-type (WT) metastatic colorectal cancer (mCRC): Results from the phase 3 PARADIGM trial.

Abstract: LBA1 Background: PARADIGM is the first prospective trial to test the superiority of PAN vs. BEV in combination with standard doublet first-line chemotherapy for patients (pts) with RAS WT mCRC and left-sided primary tumors. Methods: This open-label, multicenter trial in Japan (NCT02394795) randomly selected pts with chemotherapy-naive RAS WT mCRC to PAN + mFOLFOX6 or BEV + mFOLFOX6. Overall survival (OS) as primary endpoint was hierarchically tested in patients with left-sided tumors, followed by those in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…Furthermore, in the PARADIGM study, the secondary resection rate was 16.5% and 10.9% in the panitumumab and bevacizumab arms, respectively. 17 Our study indicated that anti-EGFR mAb plus chemotherapy led to significantly higher secondary resection rates, regardless of the primary tumor location, which was compatible with the results in the PARADIGM study. Because of the retrospective nature of our study, we could not adjust for other critical confounding factors, such as tumor size and metastatic site.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, in the PARADIGM study, the secondary resection rate was 16.5% and 10.9% in the panitumumab and bevacizumab arms, respectively. 17 Our study indicated that anti-EGFR mAb plus chemotherapy led to significantly higher secondary resection rates, regardless of the primary tumor location, which was compatible with the results in the PARADIGM study. Because of the retrospective nature of our study, we could not adjust for other critical confounding factors, such as tumor size and metastatic site.…”
Section: Discussionsupporting
confidence: 90%
“…In the DEEPER trial, cetuximab in combination with triplet chemotherapy induced significantly deeper tumor responses compared with bevacizumab plus a chemotherapy triplet 35 ; however, the secondary resection rate was similar between the two arms. Furthermore, in the PARADIGM study, the secondary resection rate was 16.5% and 10.9% in the panitumumab and bevacizumab arms, respectively 17 . Our study indicated that anti‐EGFR mAb plus chemotherapy led to significantly higher secondary resection rates, regardless of the primary tumor location, which was compatible with the results in the PARADIGM study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Third, the sample size in subgroups was limited and the hypothesis-generating results do not allow for definite conclusion. Validation of our findings in other-ideally bigtrials with randomized anti-EGFR antibody maintenance therapy or at least random assignment of the antibody within the regimen such as the PARADIGM trial 31 will add to the level of evidence. Fourth, a potential selection bias by pretreatment with Pmab 1 FOLFOX as induction treatment might have occurred, which subsequently might have led to selection of patients with favorable outcomes only-limiting the generalizability of the observations.…”
Section: Discussionmentioning
confidence: 59%
“…Location of primary tumor has also been shown to impact prognosis and response to anti-EGFR therapy, with retrospective analyses from the Intergroup 80405, CRYSTAL, FIRE-3, PEAK, PRIME, and PARADIGM trials showing that patients with left-sided tumors, but not those with right-sided tumors, benefited from the addition of anti-EGFR therapy to their treatment (Yoshino, and , 2021). [43][44][45] Incorporation of cetuximab or panitumumab with FOLFIRI or FOLFOX are now standard of care first-line treatment options in Canada for patients with mCRC who have leftsided primary tumors and are RAS wild-type.…”
Section: Extended Ras Testing (Including Kras and Nras)mentioning
confidence: 99%